Analisis Perbandingan Penerapan E-Form dan E-Filing dalam Pelaporan Surat Pemberitahuan Tahunan pada Kantor Konsultan Pajak - Firdaus Salsabila; Vicky Vendy (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to find differences or gaps in the use of electronic SPT in paying taxes with e-filing and e-form services. This research uses a qualitative approach with a case study method. The informants used in this research are tax consultants who have experience in using both types of electronic SPT. The comparison is that if e-filing was launched in 2004, the form filling process was carried out via the official website of the Directorate General of Taxes, and was used for individual taxpayers who had income under IDR 60,000,000.00 using the SPT 1770SS form. Meanwhile, e-form is a development of the E-SPT application which has been used since 2017, the filling process is carried out offline by downloading the form first via the Directorate General of Taxes website, used for individual taxpayers who have income from more than more than one employer and use the SPT form 1770, Individual Taxpayers who have income of more than IDR 60,000,000.00 and use the SPT 1770S form, or Corporate Taxpayers who use the SPT 1771 form.